Acyl-CoA-binding protein as a driver of pathological aging - Léa Montégut; Flavia Lambertucci; Lucas Moledo-Nodar; Carmen Fiuza-Luces; Carlos Rodríguez-López; Jose Antonio Serra-Rexach; Sylvie Lachkar; Omar Motiño; Mahmoud Abdellatif; Sylvère Durand; Fanny Aprahamian; Vincent Carbonnier; et al. (Proceedings of the National Academy of Sciences, 2025)
The tissue hormone acyl coenzyme A–binding protein (ACBP, encoded by the gene diazepam-binding inhibitor , DBI) has been implicated in various facets of pathological aging. Here, we show that ACBP plasma concentrations are elevated in (close-to-)centenarians (mean ± SD age 99.5 ± 4.5 y) commensurate with their health deterioration, correlating with a reduced glomerular filtration rate and a surge in senescence-associated cytokines. ACBP neutralization by means of a monoclonal antibody (mAb) improved health span in a strain of progeroid mice. In a mouse model of chronic kidney injury induced by cisplatin, anti-ACBP mAb administration counteracted both histopathological and functional signs of organ failure. ACBP inhibition also prevented the senescence of tubular epithelial cells and glomerular podocytes induced by cisplatin or doxorubicin, respectively, as measurable by the immunohistochemical detection of cyclin-dependent kinase inhibitor 1A (CDKN1A, best known as p21). Senescence was also prevented by anti-ACBP mAb treatment in additional mouse models of accelerated aging. This applied to liver damage induced by a combination of high-fat diet and carbon tetrachloride, where hepatic cells become senescent. Moreover, administration of anti-ACBP mAb prevented natural and doxorubicin-accelerated cardiomyocyte senescence. We performed single-nucleus RNA sequencing to study the transcriptome of hearts that had been exposed to doxorubicin and/or anti-ACBP in vivo. In cardiomyocytes, doxorubicin caused an anti-ACBP-reversible dysregulation of mRNAs coding for cardioprotective proteins involved in autophagy, fatty acid oxidation, mitochondrial homeostasis, and oxidative phosphorylation. Altogether, these findings plead in favor of a broad age-promoting effect of ACBP across different organ systems.